RATIONALITIES IN EDUCATION TEACHER OF PHYSICAL EDUCATION: THE HISTORICITY IN UNIVERSITY (Fiep Bulletin - online, 2016)
Presents a discussion about the meta-analysis focused on teacher training in order to verify the rationality of researchers in addressing the training of physical education teachers. Anchored in the qualitative approach, the study works at triangulation of research instruments. Namely: a) empirical data from longitudinal research (2001-2006); b) literature review and; c) meta-analysis of articles published in FIEP Bulletin Online (2010-2014). The latter two cases were treated in the academic and scientific analysis of the dimensions proposed by Novikoff (2010) texts table. Of the 1470 articles found, 108 contained crawlers "teacher education", "higher education" (6) and "knowledge / wisdom" (5). The rationales were distributed 1) techniques with instrumental and normative values ??that reinforce knowledge - regulation were given in 87% of articles and; 2) critical rationality with normative values ??and professional partners, with an emphasis on knowledge-autonomy which considers training / thinking in the humanities and social issues, by approximately 23%. While recurring theme in / on several research groups, teacher training is accentuating its epistemological and historical aspects. And this discussion is possible revision in policy for the training of physical education teachers, especially in courses of private higher education is clearly an important area of ??training, but still lacks autonomy, as is revealed in the historicity of the expansion Brazilian higher education. We intend to contribute with other scholars and groups that organize for continuous and thorough discussion and communication on the topic in the area of Physical Education, a collaborative environment. We believe this is the proposal of the International Congress of Physical Education and FIEP World Congress.
Keywords: Teacher Training; Rationalities; Higher Education.